2020
DOI: 10.2141/jpsa.0190068
|View full text |Cite
|
Sign up to set email alerts
|

Use of Starch Granules Enriched with Carvacrol for the Lesser Mealworm, <i>Alphitobius diaperinus</i> Control in Chicken House: Effects on Insects and Poultry

Abstract: The aim of this study was to investigate the effect of starch granules enriched with carvacrol and mixed with straw pellets (as poultry litter) on the mortality of larvae and adults of the lesser mealworm, Alphitobius diaperinus Panzer, a cosmopolitan pest inhabiting chicken houses in vast numbers worldwide. Additionally, the effect of starch granules on the growth parameters and survival of broiler chickens exposed to treated litter was examined. In this study, granules containing 3, 5, and 10% carvacrol was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 29 publications
(20 reference statements)
0
6
0
2
Order By: Relevance
“…Additionally, water was used as a starch modifier because it limits the upper processing temperature (27). Our earlier study also proved that 5% carvacrol is enough to protect chickens from insects such as the lesser mealworm, Alphitobius diaperinus Panzer (24).…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…Additionally, water was used as a starch modifier because it limits the upper processing temperature (27). Our earlier study also proved that 5% carvacrol is enough to protect chickens from insects such as the lesser mealworm, Alphitobius diaperinus Panzer (24).…”
Section: Introductionmentioning
confidence: 82%
“…Carvacrol is an essential oil which has very strong antifungal, antiviral and antimicrobial effects and can reduce the population of parasites responsible for gastrointestinal diseases (1,5,6,11,17,19,22,30). Our previous studies also showed that carvacrol significantly impaired the growth and development of Alphitobius diaperinus larvae and is toxic to this pest (24). Because of carvacrol's properties, it was selected as a litter additive to assess whether the addition of it may have a beneficial impact on the efficiency of nutrition and on the health status and condition of animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A complexidade das condições internas das instalações, biologia e comportamento da praga, bem como a presença das aves, tornam as medidas de controle mais restritivas e são aspectos que propiciam baixa eficiência nos métodos de controle utilizados (RODRIGUES, 2019;SZCZEPANIK et al, 2020). Nesse sentido, apenas o emprego de medidas como, remoção e/ou substituição de partes úmidas da cama (cascão), remoção do excesso de esterco e retirada de aves mortas, não são suficientes para redução significativa das populações infestantes (RODRIGUES, 2019).…”
Section: Controle Do Cascudinhounclassified
“…Devido à influência negativa sobre as aves nos galpões, normalmente as medidas curativas de controle são efetuadas durante o vazio sanitário entre os lotes de frango que são geralmente fundamentadas no uso de inseticidas, principalmente químicos sintéticos à base de piretroides e organofosforados (ALVES, et al, 2006;FERREIRA, 2018;SOUZA et al, 2020;SZCZEPANIK et al, 2020).…”
Section: Controle Do Cascudinhounclassified